Non-parametric identication of the mixed proportional hazards model with interval-censored durations - Christian N. Brinch (Statistics Norway, Research Department, 2009)
This note presents identication results for the mixed proportional hazards model when duration data are interval-censored. Earlier positive results on identication under intervalcensoring require both parametric specication on how covariates enter the hazard functions and assumptions of unbounded support for covariates. New results provided here show how one can dispense with both of these assumptions. The mixed proportional hazards model is non-parametrically identied with interval-censored duration data, provided covariates have support on an open set and the hazard function is a non-constant continuous function of covariates.
Keywords: C41; 330; duration analysis; interval-censoring; non-parametric identication